Rotating Thin-Shell Wormhole - Övgün, Ali (SpringerLink, 2016)
We construct a rotating thin-shell wormhole using a Myers-Perry black hole in five dimensions, using the Darmois-Israel junction conditions. The stability of the wormhole is analyzed under perturbations. We find that exotic matter is required at the throat of the wormhole to keep it stable. Our analysis shows that stability of the rotating thin-shell wormhole is possible if suitable parameter values are chosen.
The file in this item is the post-print version of the article (author’s copy; author’s final manuscript, accepted for publication after peer-review process). Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: black hole; wormhole; thin-shell; rotating black holes; Myers-Perry; Darmois-Israel junction conditions